Hardwiring the OS Kernel into a Java Application Processor - Tsai, Chun-Jen; Lin, Cheng-Ju; Chen, Cheng-Yang; Lin, Yan-Hung; Ji, Wei-Jhong; Hong, Sheng-Di (My University, 2017)
This paper presents the design and implementation of a hardwired OS kernel circuitry inside a Java application processor to provide the system services that are traditionally implemented in software. The hardwired system functions in the proposed SoC include the thread manager, the memory manager, and the I/O subsystem interface. There are many advantages in making the OS kernel a hardware component, such as a fast system boot time, highly efficient single-core multi-thread context-switching performance, and a better potential for supporting a complex multi-level memory subsystem. In addition, since the target application processor used in this paper is based on a Java processor, the system is not susceptible to the stack and pointer-based security attacks that are common to the register-based processors. Full-system performance evaluations on an FPGA show that the proposed system is very promising for deeply-embedded multi-thread applications.
Keywords: Hardware thread mangers; Hardware memory managers; Java processors; Embedded application processors